Fire Vulnerability Assessment using Multicriteria Analysis in Makassar City - Nanda Mutiara Zani; Azizah Putri Abdi; Nur Zahrah Afifah; Iqbal Kamaruddin; Amiruddin Akbar Fisu (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2022)
The safety aspect, especially the fire disaster, is essential for Makassar City because of its role as a metropolitan city and a center of activity in the Eastern Indonesia Region. The dense population and activities make Makassar City vulnerable to fires. A vulnerability assessment can assist in urban disaster management, especially in highlighting areas of fire disaster mitigation.Based on this urgency, this study aims to identify fire-prone areas in Makassar City. This study examines the fire vulnerability of Makassar City from population density, building density, frequency of previous fire events, fire fires, distance to the availability of clean water, and dangerous buildings. Fire susceptibility criteria are based on stakeholder assessments involving disaster experts, city planners, and firefighters through the Analytical Hierarchy Process. Spatial assessment using multi-criteria analysis through the Simple Additive Weighting method, which is integrated with the Geographic Information System to allow spatial weighting. The study results show that the western and northern parts of Makassar City are very prone to fires. This area is an early development area for Makassar City, characterized by a dense population and buildings with various activities.